Stereotypes and prejudices in the Italian L2 class. A conversation analysis of their emergence in teachers’ talk - Nasi, Nicola; Caronia, Letizia (Education Sciences & Society - Open Access, 2023)
The paper explores teachers’ interactional uses of stereotypes and prejudices in the Italian L2 classroom. Drawing from video-ethnographic research in a voluntary association, this study adopts a discursive approach to stereotypes and prejudices, analyzing their pragmatic uses during classroom activities. Even though previous literature has mostly argued against these social devices, the analysis illustrates that teachers make use of stereotypes and prejudices to pursue their local aims in the classroom. Specifically, teachers mobilize stereotyped talk to achieve specific social and didactic aims (e.g., to explain a lexical items or to prompt laughter). In the discussion, we critically consider the risks and opportunities of this kind of practice and advance few implications for teachers’ professional practice, arguing for the relevance of video-based teacher training.